The Analysis of the Emergence and Development of Female Entrepreneurship in Romania - Ardelean, Dorina; Pribac, Loredana; Haiduc, Cristian; Anghelina, Andrei (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The emergence of the female entrepreneurial social class is certain and convincing in many countries, including Romania. Through this study we wish to portray a relevant image regarding the situation of female entrepreneurship in Romania. The starting point and a question to which many seek answers are: What was and is the economic strength of female entrepreneurship in Romania? After a short historical presentation regarding the evolution of feminine entrepreneurship, we presented the analysis of results after 25 years of democracy and capitalism. The main inference that we have deducted was: that the number of female entrepreneurs is on ascending path.